(untitled) (Current Horticulture, 2024)
Tuberose (Polianthes tuberosa L.) is popular flower crop due to its exquisite beauty and strong fragrance. However, as a potential ornamental plant resource, it has not been well commercialized. This crop has the potential to develop and expand the ornamental horticultural industry if properly managed and exploited. Tuberose longevity and quality are influenced by production and post- production factors. The production factors provide an excellent opportunity to overcome all the imbalances of post-harvest management. Therefore, all important aspects of production factors of tuberose cultivation for better understanding and future strategies for improved flower quality and Post-harvest life have been discussed. These information are important for both farmers and distributors.